Furthering extraction of torsional–flexural frequencies for thin-wall beams from the rocking motion of a two-wheel test vehicle. (June 2022) - Shi, K.; Mo, X.Q.; Xu, H.; Wang, Z.L.; Hu, X.S.; Yang, Y.B.
Abstract: This paper proposes a furthering approach for extracting the first several flexural and torsional–flexural frequencies of thin-walled box girders from the residual contact response of a two-wheel test vehicle passing the bridge. Unlike most previous studies, the single-axle test vehicle is modeled as a two degree-of-freedom (DOF) system to account for the two wheels' rocking motion, which relates to torsional–flexural motion of the beam. To start, a new theory for the mono-symmetric thin-walled beam subjected to a two-wheel moving vehicle is presented. The wheel contact response derived herein (which is free of vehicle frequencies) enables us in the first stance to remove the overshadowing effect on bridge frequencies brought by outstanding vehicle frequencies. The other concern in extracting the bridge frequencies is the noises posed by random pavement roughness, which is overcome through the use of the residual contact response generated by two identical connected vehicles. This paper furthers the existing ones in that the wheel response (i.e. the vehicle's rocking motion) is utilized to extract the torsional–flexural frequencies of the bridge, making use of the linking action between the vehicle's two wheels and the bridge's cross section. The reliability of the theory and proposed technique is numerically validated for parameters such as damping of the vehicle and bridge, bridge/vehicle mass and frequency ratios, pavement roughness, and vehicle speed. It was confirmed that the proposed technique is capable of extracting the first several flexural and torsional–flexural frequencies of the thin-walled beam, including some higher conjugate modes, for all the cases studied herein. Highlights: New approach for extracting torsional–flexural frequencies for thin-wall beams from the rocking motion of a two-wheel test vehicle. New closed-form solutions for the system responses for thin-walled beams acted upon by a moving vehicle's two wheels. Suppress vehicle' self frequencies by contact response and bridge's roughness by residual response of two connected vehicles. Identify first few flexural and torsional–flexural frequencies from wheels' contact response.